A comparative study on N-mineralization of leguminous tree leaves and its influence on the growth and yield of rice in acid sulfate soil - Nukoon Tawinteung; Upasena, S. H.; Sumitra Poovarodom; Preeda Pakpian; Royal Thai Government (Bangkok : Asian Institute of Technology, 1995)
A comparative study on N mineralization of leguminous tree leaves and their influence on growth and yield of rice was conducted on acid sulfate soil, during the dry season from January to May 1995 . The seven green manures, Leucaena leucocephala, Delonix regia, Samanea saman Peltophorum pterocapum, Acacia auriculiformis Cassia siamea and Sesbania grandiflora at the rate 100 kg N ha-1 and chemical fertilizer recommended by Department of Agriculture (16-20-0+ Urea) at the rate 62.8 kg N ha-1 were applied as the N sources for the rice (Suphanburi-90). All treatments have recei:ved 16.5 kg P ha-1 as basal. The results show that Cassia siamea, Sesbania grandiflora, Samanea saman and Leucaena leucocephala decompose fast and release more nitrogen which responded similar to DOA recommendation in terms of the rice yield. While, Delonix regia, Peltophorum pterocapum and Acacia auriculiformis decompose slowly and were similar to the control treatment. The decomposition of green manures in the soil, measured in terms of N uptake, net N mineralization, apparent N recovery by rice were significantly different due to the differences of their chemical constituents especially N, C, Lignin concentration, C:N ratio, Lignin:N ratio and Lignin + Polyphenolic: N ratio which, showed high correlation to N mineralization. Therefore, these parameter could be considered as an effective indexes for N mineralization. One year experimentation may not provide sufficient evidence to show an effect of green manure application on soil pH and organic matter content of the soil.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Environment, Resources, and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1995
Keywords: Rice -- Soils; Rice -- Fertilizers